Cráneo en trébol y fisura facial bilateral - Alvarez Manassero, Denisse (2015)
Introduction Cloverleaf skull syndrome, or Kleeblattschädel syndrome, is a rare malformation in which the skull has a cloverleaf appearance. It is caused by the premature closure of several sutures, being evident before birth. Objective To present our experience in a case of cloverleaf skull syndrome, and update the information from the literature. Clinical case A female infant of 5 months of age, diagnosed at birth with cleft lip and palate and hydrocephaly. A peritoneal ventricle valve was implanted at 30 days of life, and an ocular enucleation was performed due to an infectious process. The patient was followed-up in Genetics, where it confirmed a macrocephaly and craniosynostosis type cloverleaf skull. The 46XX cytogenetic study and echocardiography were normal. The brain CT scan showed multiple anomalies associated with hydrocephaly and non-specific malformations. Conclusion Cloverleaf skull may be present in isolated form or associated with other congenital abnormalities, leading to various craniosynostosis syndromes, such as Crouzon, Pfeiffer or Carpenter. It may also be a component of the amniotic rupture sequence or to different dysplasias, such as campomelic dysplasia, thanatophoric dysplasia type 2, or the asphyxiating thoracic dystrophy of Jeune. The case presented does not fulfil all the characteristics needed to be included within a specific syndrome, and on not having a family history that suggests a hereditary pattern or chromosome abnormalities, it is concluded that it is a case of a congenital anomaly of sporadic presentation.